2016
DOI: 10.5935/abc.20160133
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Phenotypic Expression of Mutations in the MYH7, MYBPC3 and TNNT2 Genes in Families with Hypertrophic Cardiomyopathy in the South of Brazil: A Cross-Sectional Study

Abstract: Background:Mutations in sarcomeric genes are found in 60-70% of individuals with familial forms of hypertrophic cardiomyopathy (HCM). However, this estimate refers to northern hemisphere populations. The molecular-genetic profile of HCM has been subject of few investigations in Brazil, particularly in the south of the country.Objective:To investigate mutations in the sarcomeric genes MYH7, MYBPC3 and TNNT2 in a cohort of HCM patients living in the extreme south of Brazil, and to evaluate genotype-phenotype ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 47 publications
0
7
0
Order By: Relevance
“…Several genetic studies have found an association between LVD and dilated cardiomyopathy (DCM). Various sarcomeric protein-encoding genes such as cardiac myosin-binding protein C (MYBPC3), myosin heavy polypeptide, and cardiac troponin I gene mutations, as well as other gene mutations have been identified in DCM [7][8][9][10][11][12][13]. The common sarcomeric gene polymorphisms with their locations and functional roles are given in Table 1.…”
Section: Common Sarcomeric Protein and Associated Gene Polymorphismmentioning
confidence: 99%
See 1 more Smart Citation
“…Several genetic studies have found an association between LVD and dilated cardiomyopathy (DCM). Various sarcomeric protein-encoding genes such as cardiac myosin-binding protein C (MYBPC3), myosin heavy polypeptide, and cardiac troponin I gene mutations, as well as other gene mutations have been identified in DCM [7][8][9][10][11][12][13]. The common sarcomeric gene polymorphisms with their locations and functional roles are given in Table 1.…”
Section: Common Sarcomeric Protein and Associated Gene Polymorphismmentioning
confidence: 99%
“…Mutations in the TNNT2 gene have been positively associated with DCM and familial HCM [20,74,75]. It has been reported that a 5-bp (CTTCT) I/ D polymorphism present in intron 3 of the TNNT2 gene may impair the skipping of exon 4 and lead to LVD [10,19,20].…”
Section: Troponinsmentioning
confidence: 99%
“…The constructed heredogram revealed 30 relatives, over five generations, in which only one unexplained death of a 30-year-old female with no HCM diagnosis was detected ( Figure 2 ). 14 …”
Section: Resultsmentioning
confidence: 99%
“…However, several other genes have already been associated to this disease 5,14 , which are yet to be investigated.…”
Section: Discussionmentioning
confidence: 99%
“…Molecular-genetic testing was performed in 18 (20%) patients, whose results were previously published. 18 Diagnosis was established according to the current guidelines 15,17 based on the identification of unexplained LV hypertrophy detected on echocardiogram and/or magnetic resonance imaging by the presence of MLVWT ≥15 mm measured at any segment, with septum/ posterior wall ratio ≥1.3 in the absence of chamber dilation or other conditions capable of producing a similar pattern of hypertrophy. Eighteen cases were excluded due to a follow-up period <12 months or previous history of cardiopulmonary arrest, ventricular fibrillation or ventricular tachycardia with hemodynamic impairment.…”
Section: Patient Selectionmentioning
confidence: 99%